PHYSICAL EDUCATION IN NEW ZEALAND SECONDARY SCHOOLS - JONES, GRANT C. (Fiep Bulletin - online, 2014)
In New Zealand, secondary schools cater for students 13-18 years of age, and physical education and health is a compulsory part of the curriculum. This will be a PowerPoint presentation which will show some of the practical aspects of the Physical Education Curriculum, which focus on the learning of movement concepts and improving motor skills through a range of physical activities. The physical activities include sports, movement education and related activities, dance, cultural activities that are relevant in New Zealand, and outdoor education. These activities are seen as a vehicle to enable students to develop positive attitudes in challenging physical situations.